PENERAPAN MEDIA KARTU SOAL UNTUK MENINGKATKAN PRESTASI BELAJAR SISWA PADA POKOK BAHASAN KOLOID DI KELAS XI IPA SMA NEGERI 11 PEKANBARU - Agus Purwanto Purwanto; Elva Yasmi Amran Yasmi Amran; Rini ' (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2015)
Abstract: This research aims to increase student achievement on the subject of colloids in class XI IPA SMA Negeri 11 Pekanbaru. Form of research is experiment research with pretest-posttest design. The sample consisted of two classes, XI IPA1 as an experiment class and XI IPA2 as a control class randomly selected after tests of normality and homogeneity. Experiment class was given to applied question card media while the control class was not. Data analysis technique is used t-test. Based on the results of final processing data use t-test formula obtained  tcount>ttable is  3,06>1,67, it means that the applying of question card media can improve student achievement on the subject of colloids in class XI IPA SMA Negeri 11 Pekanbaru. The category improvement of student achievement in experiment class was high category with a score gain normalized is 0,73. Keywords : Question card media, Learning achievement